Epidemiological and clinical profile of Laboratory confirmed cases of COVID 19 admitted in Tertiary care Hospital Jammu, Jammu & Kashmir - Sultan, Asheeb; Kumari, Rashmi; Gupta, Rajiv Kumar; Langer, Bhavna; Zargar, Tasneef; Mir, Mehak Taban (Indian Journal of Community Health, 2022)
Background: Three or more waves of COVID 19 pandemic have hit the different parts of world including India very hard, taking toll on the lives of people both in terms of morbidity and mortality. Keeping this in mind, the present study was conducted with an aim to determine the socio-demographic and clinical profile of laboratory confirmed COVID 19 cases and to determine their association with oxygen requirement and outcome of disease at the time of discharge. Methods: The present cross-sectional study was conducted on lab confirmed COVID 19 cases admitted in tertiary care hospital in Jammu from June-July 2021.Data was collected using convenient sampling method. The self-designed questionnaire used for data collection obtained information regarding socio-demographic characteristics of patients as well as clinical features of the disease. Results: Out of total 161 patients studied, 60.8% were males and 39.2% were females. Mean age was 51.2 ± 17.5 years. Comorbid conditions were present in 37.8% patients, with hypertension being the most common ( 36%). Cough, Fever, breathlessness and myalgia were the main presenting symptoms (90%, 81%, 57.7% and 56% respectively). The variables which were found to have statistically significant association with oxygen requirement and the outcome of disease at the time of discharge were age, gender and presence of co-morbidity (p <0.05). Conclusions: Advancing age, male gender and presence of underlying co-morbidity were found to be significant risk factors for the requirement of oxygen and poor outcome of the disease.